Ontological Classifications and Human Rationality in Bioethics. Issue 4 (29th July 2019) - Romanyshyn, Alexandra T
Abstract: Metaphysics often has an important role in deciding ethical questions. Specifically, in the realm of bioethics, metaphysical questions such as the nature of persons, diseases, and properties in general can be crucial to determining what is right or wrong. In this article, I tie together various metaphysical themes that recur throughout the rest of the issue: rationality as an element of human nature, ontological classifications, and kinds of action. I will explain that each has ethical implications. Actions that contravene reason will be morally problematic, whereas our classification of illnesses will have important implications for how we ought to respond to ill persons. Metaphysical questions appear, or are at least suggested, in each article, pointing to the need for metaphysics in answering bioethical questions.